Evaluating the effectiveness of mass drug administration on lymphatic filariasis transmission and assessment of post-mass drug administration surveillance in Nigeria’s Federal Capital Territory - Juliana Ajuma Amanyi-Enegela; Joseph Kumbur; Faizah Okunade; Donald Ashikeni; Rinpan Ishaya; Girija Sankar; William Enan Adamani; Moses Aderogba; Louise Makau-Barasa; Achai Emmanuel; Bosede Eunice Ogundipe; Chinwe Okoye; et al. (Infectious Diseases of Poverty)
Abstract Background Nigeria’s Federal Capital Territory (FCT) launched annual mass drug administration (MDA) in its four lymphatic filariasis (LF)-endemic councils in 2011, achieving sustained high coverage and pre-transmission assessment survey success. This study aimed to confirm transmission interruption in Bwari and Gwagwalada and to evaluate post-MDA surveillance efficacy in Abaji and Kuje. Methods Transmission Assessment Surveys (TAS) were systematically conducted in four distinct evaluation units (EUs) within the FCT. TAS 1 was carried out in Bwari and Gwagwalada EUs that had recently achieved pre-TAS thresholds indicating potential interruption of transmission, whereas TAS 2 was conducted in Abaji and Kuje EUs, where MDA had been discontinued since 2021 following successful TAS 1 evaluations. Abbott Filarial Test Strips (FTS) were employed to test children aged 6–7 years attending selected schools. Data collection adhered to standardized WHO guidelines, utilizing both paper-based and electronic data-capture tools to enhance accuracy and reduce human error. Results A total of 6,448 children participated in surveys across the four EUs, with gender distribution closely balanced (53% male, 47% female). In TAS 1 (Bwari and Gwagwalada), no LF-positive cases were identified well below the WHO-defined critical cutoff of 18 cases. In TAS 2 (Abaji and Kuje), a single LF-positive case was detected in Abaji, still below the critical threshold. Participant refusal rates were minimal, reflecting strong community support and engagement. Conclusions The findings provide compelling evidence of significant progress toward LF elimination in Nigeria’s FCT; however, the single positive case in Abaji underscores the continued importance of vigilant surveillance and integrated vector-management strategies to maintain elimination status and guard against residual transmission.